O Professor da educação profissional e a conectividade orgânica entre formação e prática docente: um estudo sobre o IFET Sudeste de Minas Gerais - Lecir Jacinto Barbacovi (2011)
This is a research of teacher education and professional education in Brazil, focusing on teachers who work at the Federal Institute of Education, Science and Technology - ÍFET - Southeast of Minas Gerais. We conducted a research on work and dissertation thesis, defended between 1998 to 2009, available on the portal capes, from which weidentify the central themes they have focused and some of its main results. This research was the scenario within which this study is a part. Through field research conducted on campuses Barbacena, Juiz de Fora and Rio Pomba, we collect information through documentary analysis, questionnaire given to 128 teachers and interviews conducted with nine teachers deepening. The theory was developed, based on the contributions of the precursors of the critical reflective - Giroux, Tardif, andNóvoa Perrenoud - helping us to understand the intrinsic relationship between theory and practice. As a methodology, we rely on theoretical and conceptual mapping, and it identified the core issue and overall purpose of the study were stratified into dimensions, subdimensions, components and indicators. The information needed to research were captured by these indicators, or items, from which, in a motion for reinstatement, we reconstitute the core variables, allowing the crossings due. The data produced and processed in the midst of the theoretical framework, allowed us to identify the academic and professional profile of teachers working in professional education. In turn, these studies have revealed that the process of constitution of their teacher education is marked predominantly by developing professional practice and recognize the importance of small initial training or continuing in this constitution. Given our knowledge and teaching practice, have different positions related to the design reflective indicated at specific levels: beginner, intermediate and advanced. This stratification is understood in this context as an interim stage. Verified in this investigation, that the modalities used for the assessment - sub dimension of teachingpractice - are directly related to the undergraduate course completed. Through this study we can say that the teaching practice and is positively associated with statistical significance, with professional attitude in the face of teacher knowledge, which in turn is not built specifically through the courses of initial and continuing training, but with them. There is therefore no training, but training and produces joints that contains theoretical and practical grounds is that the constitution process of teaching. Thus, organizational connectivity between theory and practice, between a continuous process of training and teaching practices in context is the core that forms the reflective teacher.